Understanding molt control switches: Transcriptomic and expression analysis of the genes involved in ecdysteroidogenesis and cholesterol uptake pathways in the Y-organ of the blue crab, Callinectes sapidus. - Elena Legrand (Public Library of Science (PLoS), 2021)
The crustacean molting process is regulated by an interplay of hormones produced by the eyestalk ganglia and Y-organs (YO). Molt-inhibiting hormone and crustacean hyperglycemic hormone released by the sinus gland of the eyestalk ganglia (EG) inhibit the synthesis and secretion of ecdysteroid by the YO, hence regulating hemolymph levels during the molt cycle. The purpose of this study is to investigate the ecdysteroidogenesis pathway, specifically genes linked to changes in ecdysteroid levels occurring at early premolt (ePM). To this end, a reference transcriptome based on YO, EG, and hepatopancreas was de novo assembled. Two genes (cholesterol 7-desaturase Neverland and cytochrome p450 307a1-like Spook) involved in ecdysteroidogenesis were identified from the YO transcriptome using sequence comparisons and transcript abundance. Two other candidates, Hormone receptor 4 and probable cytochrome p450 49a1 potentially involved in ecdysteroidogenesis were also identified. Since cholesterol is the ecdysteroid precursor, a putative cholesterol carrier (Apolipoprotein D-like) was also examined to understand if cholesterol uptake coincided with the increase in the ecdysteroid levels at the ePM stage. The expression level changes of the five candidate genes in the YO were compared between intermolt (IM) and induced ePM (iePM) stages using transcriptomic analysis. Expression analysis using qPCR were carried out at IM, iePM, and normal ePM. The increase in Spook and Neverland expression in the YO at the ePM was accompanied by a concomitant rise in ecdysteroid levels. The data obtained from iePM stage were congruent with those obtained from the normal ePM stage of intact control animals. The present findings support the role of Halloween genes in the ecdysteroidogenesis and molt cycle in the blue crab, Callinectes sapidus.